2016
DOI: 10.1016/j.phrp.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Two Methods of Cryotherapy and Intense Pulsed Light with Triamcinolone Injection in the Treatment of Keloid and Hypertrophic Scars: A Clinical Trial

Abstract: ObjectivesKeloid and hypertrophic scars are abnormal manifestations of wounds that occur following skin injuries in the form of local proliferation of fibroblasts and increased production of collagen. There are several ways to cure these scars; treatment must be selected based on the nature of the scars. In this clinical trial, two methods—cryotherapy and intense pulsed light (IPL)—are compared in the treatment of scars, and the results are presented in terms of improvement level, complications, and patient sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Although a variety of surgical and nonsurgical methods have been used to treat hypertrophic scars and keloids, [ 13 15 ] intralesional steroid injections remain the standard treatment. [ 16 ] Mean scar volumes were reduced from baseline values of 0.73 ± 0.701 to 0.14 ± 0.302 mL after repeated monthly intralesional injections of triamcinolone acetonide. [ 17 ] Pain, however, which affects patient compliance, inevitably has an impact on the effectiveness of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of surgical and nonsurgical methods have been used to treat hypertrophic scars and keloids, [ 13 15 ] intralesional steroid injections remain the standard treatment. [ 16 ] Mean scar volumes were reduced from baseline values of 0.73 ± 0.701 to 0.14 ± 0.302 mL after repeated monthly intralesional injections of triamcinolone acetonide. [ 17 ] Pain, however, which affects patient compliance, inevitably has an impact on the effectiveness of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Meymandi et al in a comparative study found that cryotherapy as well as intense pulse light laser were equally effective in treatment of hypertrophic scar and keloid [11]. Cryotherapy in combination with intralesional steroid has been the most popular classic treatment for both keloid and hypertrophic scars.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid nitrogen is commonly used to treat keloids, Meymandi et al carried out a clinical trial where cryotherapy sessions of 10 seconds with liquid nitrogen was performed using 1 mg/cm 2 triamcinolone acetonide injection mixed with lidocaine (50:50 ratio), showing a treatment response rate of 75% [28]. The most common adverse effect reported was hyperpigmentation.…”
Section: Cryotherapymentioning
confidence: 99%
“…As the first oral multi-kinase inhibitor, sorafenib blocks multiple intracellular signaling pathways involving keloid signaling. In 2016, Wang et al conducted a controlled study to observe the interaction of sorafenib, in which it was shown to act as an effective inhibitor of transforming growth factor-beta (TGF-β)/Smad and mitogen-activated protein kinase/extracellular-signal-regulated kinase (MAPK/ERK) in vitro [28]. This resulted in decreased expression of connective tissue growth factor (CTGF), interleukin-6 (IL-6), and interleukin-8 (IL-8), preventing keloid fibroblast migration and proliferation, as well as angiogenesis and collagen accumulation, which presented as the first step of favorable results by inhibiting keloid healing signaling pathways [30].…”
Section: New Strategies and Clinical Usementioning
confidence: 99%